A Study on the Impact of Cross-border Logistics and Online Reviews on the Performance of Cross-border Export E-commerce Firms - Chen, Junyang (Economics & Management Review, 2024)
China’s cross-border e-commerce trade is a key driver of the country’s economic growth and plays a significant role in promoting the transformation and development of foreign trade. Currently, many cross-border e-commerce companies in China face several challenges, including unstable logistics, high costs of establishing overseas warehouses, language barriers and fraudulent online reviews. This paper examines the relationship between cross-border logistics, online reviews, and enterprise performance by summarizing the research of domestic and international scholars which can be deduced that: (1) The impact of online reviews on cross-border e-commerce businesses is significant; (2) Cross-border e-commerce business performance can be driven to a certain extent by excellent cross-border logistics; (3) Online reviews and cross-border logistics have a mutually influential relationship in their development and operation. The article further analyses that under the status quo of rapid development of cross-border e-commerce, enterprise management’s perfect operation mechanism and favorable national policies will also have a positive impact on the performance improvement of Chinese cross-border e-commerce enterprises. Finally, the author presents conclusions and countermeasure suggestions for the main problems in the development of Chinese cross-border e-commerce enterprises by combining existing literature and research results from both domestic and international sources.